The utilization of fly ash for the production of strengthened bricks / Mohamad, N, F ...[et al.] - N, F, Mohamad; D.A, Mat Yusof; M.S, Ismail; N., Mohamed; N.F, Ahmad Shairazi; M.S.I, Mohamed Elham
Modem buildings all over the world are made of either bricks or concretes. The demand of these two materials are so high. Therefore, companies all over the world are squeezing every bit of profit out of the production of these two materials. Cement companies like Lafarge, Holcim and YTL Cement have been producing these materials out of cement, besides discovering new techniques that can enhance the properties of the raw materials. As a result, it turned out to be strengthened. Nowadays, the utilization of fly ash is becoming more and more prominent over time. This is due to the fact that fly ash has cementitious properties. Therefore, it can drastically increase the strength of cement, thus creating strengthened bricks or strengthened concrete. However, fly ash is an additive that can escalate the strength of bricks or concrete. As the name goes, fly ash is only an additive. Thus, removing the main body parts of a brick or concrete, which reducing the amounts of sand can largely reduce its strength. Therefore, the existence of the major components of a brick or concrete is of paramount importance to be taken into consideration before adding any additives, such as fly ash into it for the purpose of strength enhancement. In this study, we are using sand bricks, which include cement bricks and lime-gypsum bricks. The addition of quantities of fly ash are differentiated, but the body parts of the bricks (which include cement, lime gypsum and sand) are to be kept constant. The strength are then to be tested by using the compression test and the pores inside the bricks are to be identified by using the Ultrasonic Pulse Velocity (UPV) test, compression test and also water absorption test. Fly ash is also known as pulverized fuel ash. The major components of fly ash are silicon dioxide (SiOz), aluminium oxide (AhOJ) and calcium oxide (CaO). When coal is burnt, the remains are bottom ash and fly ash. Fly ash is a coal combustion product composed of fine particles that are driven out of the boiler with the flue gases. On the other hand, the ashes that falls at the bottom of the boiler is called bottom ash. Good quality fly ash generally improves workability with the usage of less water. The reduction in water leads to improved strength. From this findings, it can be found that fly ash bricks have improved the strength of commercialised sand bricks in terms of porosity, compression strength and also water absorption.